Gambaran Status Gizi Anak di SD Negeri 1 Poasia Kendari - Fithria Fithria; Ananda Ramadani; Wa Ode Hety Dirahayu; Citra Nurhalizah Pini; Idham Mahmud; Hadi Kalisi; Nur Sailan Andani (Jurnal Kendari Kesehatan Masyarakat, 2024)
This study aims to describe the nutritional status of children at SD Negeri 1 Poasia, Kendari City, with a focus on students aged 7 to 12 years. The method used was a survey with samples taken from 40 students. The research results showed that 32% of students were undernourished, 32% had good nutritional status, 12% were overnourished, and 22% were obese. These findings indicate significant nutritional problems, including obesity, which can be caused by an unbalanced diet and lack of physical activity. This research emphasizes the importance of nutritional education, promotion of physical activity, and collaboration between schools, parents, and the government to create an environment that supports healthy lifestyles for children